Mineral and physiochemical evaluation of cockle shell (Anadara granosa) and other selected molluscan shell as potential biomaterials - Hemabarathy Bharatham,; Md. Zuki Abu Bakar Zakaria,; Enoch Kumar Perimal,; Loqman Mohamad Yusof,; Muhajir Hamid, (Universiti Kebangsaan Malaysia, 2014)
Molluscan shells are attracting research interest due to the diverse application properties possessed. As shells are very similar to bones, this study was conducted to analyze the mineral and physiochemical composition of Cockle (Anadara granosa) shell and three other types of molluscan shell, namely Strombus canarium, Oliva sayana and Terebra dislocata as potential biomaterial for bone tissue engineering applications. Approximately 200 g of shells from each species were processed and powdered for the purpose of this study. Carbon was analyzed using the carbon analyzer while minerals and heavy metals through ICP-MS. The phase purity and crystallographic structures of the powders were identified using X-Ray Diffractometer (XRD) while the chemical functionality was determined using the Fourier transform infrared (FTIR) spectrophotometer. The analysis showed that Cockle shells contained higher content of calcium and carbon including varying amount of other minor elements comparatively. However, all four types of shell powders were found to contain below detectable levels of toxic elements. Physiochemical analysis on phase purity and crystallographic structures showed similar characteristics of carbonate group present in all four shell types. A predominantly aragonite form of calcium carbonate was detected in both XRD diffractogram and FTIR spectra for all samples. Our findings demonstrated that different types of molluscan shells have almost similar mineral and physiochemical characteristics and a predominantly aragonite form of calcium carbonate that provides a strong basis for their use as a potential bone tissues engineering material.